ABOUT THE ARTS OF ODE AND TATABBU - Feruza Nizamova (International Scientific and Current Research Conferences, 2023)
In this article, an attempt is made to study the art of ode and tatabbu. The purpose of the article is to study the ideological and artistic method in the poet's works, to determine the mastery of the ode genre, and also to determine its place in the history of Persian-Tajik literature through the analysis of ode. The ideas mentioned in the article are aimed at revealing the place and importance of literary environment and works in the development of Eastern literature.